Biomarkers of Alzheimer’s Disease Among Mexican Americans - O’Bryant, Sid E. (2013)
BACKGROUND: Mexican Americans are the fastest aging segment of the U.S. population yet little scientific literature exists regarding the Alzheimer disease (AD) among this segment of the population. The extant literature suggests that biomarkers of AD will vary according to race/ethnicity though no prior work has explicitly studied this possibility. The aim of this study was to create a serum-based biomarker profile of AD among Mexican American. METHODS: Data were analyzed from 363 Mexican American participants (49 AD and 314 normal controls) enrolled in the Texas Alzheimer’s Research & Care Consortium (TARCC). Non-fasting serum samples were analyzed using a luminex-based multi-plex platform. A biomarker profile was generated using random forest analyses. RESULTS: The biomarker profile of AD among Mexican Americans was different from prior work from non-Hispanic populations with regards to the variable importance plots. In fact, many of the top markers were related to metabolic factors (e.g. FABP, GLP-1, CD40, pancreatic polypeptide, insulin-like-growth factor, and insulin). The biomarker profile was a significant classifier of AD status yielding an area under the receiver operating characteristic curve (AUC), sensitivity (SN) and specificity (SP) of 0.77, 0.92 and 0.64, respectively. Combining biomarkers with clinical variables yielded a better balance of SN and SP. CONCLUSION: The biomarker profile for AD among Mexican American cases is significantly different from that previously identified among non-Hispanic cases from many large-scale studies. This is the first study to explicitly examine and provide support for blood-based biomarkers of AD among Mexican Americans. Areas for future research are highlighted.